Ihsan Ilahi Zahir (1945-1987) dan kritikannya terhadap pemikiran akidah Syiah / Mohd Fuad Mokhtar - Mohd Fuad, Mokhtar (2016)
“Ihsan Ilahi Zahir (1945-1987) and His Critics Towards Shiism” is a research of a profound scholar especially in the field of Shiism. This research focuses on the belief of Shiite by studying their major writings. The researcher will conduct an in-depth study of the scholar’s selected writings in order to analyze his critical thought of Shiah. The writings will be analyzed in details for the purpose of knowing his real thought over Shiism.The methods that will be used throughout this research are inductive method as well as deductive and comparative. This research is divided into six chapters with Introduction as the first chapter. The second chapter will be discussing on the historical background of the scholar Ihsan Ilahi Zahir, followed by his main criticism against the Shiite in the third chapter. His methods of criticism will be presented and analyzed in the fourth chapter. The continuation of his criticism is elaborated in chapter five and the last chapter which is chapter six would be the conclusion of the research. The finding of this research of Ihsan Ilahi Zahir’s critics towards Shiism shows that the Shi’i Imamiyyah in contrast with Islamic teaching.